If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 19 = 5x + -35 Reorder the terms: 19 + 3x = 5x + -35 Reorder the terms: 19 + 3x = -35 + 5x Solving 19 + 3x = -35 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 19 + 3x + -5x = -35 + 5x + -5x Combine like terms: 3x + -5x = -2x 19 + -2x = -35 + 5x + -5x Combine like terms: 5x + -5x = 0 19 + -2x = -35 + 0 19 + -2x = -35 Add '-19' to each side of the equation. 19 + -19 + -2x = -35 + -19 Combine like terms: 19 + -19 = 0 0 + -2x = -35 + -19 -2x = -35 + -19 Combine like terms: -35 + -19 = -54 -2x = -54 Divide each side by '-2'. x = 27 Simplifying x = 27
| 3x-2x=10 | | 7p+6m= | | 6-5x=2(3x-6) | | (9x+11)(8x-3)=0 | | -t-3=0 | | 15r-7=8 | | a^4+a^2*b^2-b^4=0 | | 7+k=4 | | 3x^2+6=54 | | 5x+8=2x-25 | | 3x^2+2=55 | | x^4=6561 | | 3x^2+2=22 | | 3x^2+2=21 | | Y=(X+4)(X-9) | | 3x^2+2=18 | | 4x^2+9=66 | | 3x^2+9=45 | | 18+5x=8x+33 | | 3x^2+9=44 | | 3x^2+9=51 | | 3x^2+9=73 | | 3a+1=7a-9 | | 3x^2+9=72 | | x^4+4x^3-2x^2-12x+3=0 | | 3x^2+9=66 | | 7x-16=5-3x | | 3x^2+6=66 | | 3x^2+6=100 | | 2x^2+6=71 | | 2x^2+6=70 | | 2x^2+6=69 |